Biomimetic and bioinspired membranes for water purification: A critical review and future directions. Issue 3 (18th March 2019) - Wagh, Priyesh; Escobar, Isabel C.
Abstract : Various types of channel proteins, broadly named porins, present in the cell membrane of gram‐negative bacteria have specific functionalities depending on their selectivity toward different nutrients or toward water. The high selectivity of porins has led to their incorporation into synthetic systems, in a field called biomimetics. An example is the addition of water channel proteins, or aquaporins, to polymeric separations membranes in order to enhance their performance in terms of selectivity and permeability. The concept of incorporating aquaporins into synthetic membranes has been studied for the last 10 years; however, there are still limitations such as costs, alignment into the membrane assembly, and scalability of membrane fabrication. Therefore, in recent years, there has been an increase in the study of synthesizing molecules with similar structure–function relationships of porins. These artificial channels attempt to mimic the biological porins, while being synthesized using simpler chemistry, being solvent compatible, and requiring less space on the membrane surface which helps to incorporate more channels into the membrane assembly. In summary, the future of biomimetic and bioinspired membranes depends on the design strategies, level of nature imitation, and the performance of these systems on a commercial scale. © 2019 American Institute of Chemical Engineers Environ Prog, 38:e13215, 2019